Spatial specificity of metabolism regulation of abscisic acid-imposed seed germination inhibition in Korean pine (Pinus koraiensis sieb et zucc) - Song, Yuan; Li, Xinghuan; Zhang, Mingyi; Xiong, Chao (Frontiers in Plant Science, 2024)
Abscisic acid (ABA) can negatively regulate seed germination, but the mechanisms of ABAmediated metabolism modulation are not well understood. Moreover, it remains unclear whether metabolic pathways vary with the different tissue parts of the embryo, such as the radicle, hypocotyl and cotyledon. In this report, we performed the first comprehensive metabolome analysis of the radicle and hypocotyl + cotyledon in Pinus koraiensis seeds in response to ABA treatment during germination. Metabolome profiling showed that following ABA treatment, 67 significantly differentially accumulated metabolites in the embryo were closely associated with pyrimidine metabolism, phenylalanine metabolism, cysteine and methionine metabolism, galactose metabolism, terpenoid backbone biosynthesis, and glutathione metabolism. Meanwhile, 62 metabolites in the hypocotyl + cotyledon were primarily involved in glycerophospholipid metabolism and glycolysis/gluconeogenesis. We can conclude that ABA may inhibit Korean pine seed germination primarily by disrupting the biosynthesis of certain plant hormones mediated by cysteine and methionine metabolism and terpenoid backbone biosynthesis, as well as reducing the reactive oxygen species scavenging ability regulated by glutathione metabolism and shikimate pathway in radicle. ABA may strongly disrupt the structure and function of cellular membranes due to alterations in glycerophospholipid metabolism, and weaken glycolysis/gluconeogenesis in the hypocotyl + cotyledon, both of which are major contributors to ABA-mediated inhibition of seed germination. These results highlight that the spatial modulation of metabolic pathways in Pinus koraiensis seeds underlies the germination response to ABA.